PROFILE OF CREATIVE THINKING ABILITIES IN CLASS VII STUDENTS OF SMPN I ADONARA BARAT - Maria Angelina Peurape; Aloisius Harso; Daniel Wolo (ScienceEdu: Jurnal Pendidikan IPA, 2020)
This study aims to determine the profile of the ability to think creatively in Science in grade VII Students of SMPN I Adonara Barat. This type of research is descriptive research. The population to 70 students, and the sample in the study was class VII A students totaling 30 students who were obtained by purposive sampling technique. Data collection using a questionnaire. The results showed that students creative thinking abilities were categorized as quite creative (47.7%). This is evidenced by the results of the descriptive analisis of the student questionnaire, namely that they are less creative (63%), higher than the number of students who are categorized as very creative (6.7%), creative (13,3%) and quite creative (17%).